Transformasi Evaluasi Pembelajaran PAI Berbasis Projek (P5) pada Kurikulum Merdeka dalam Membentuk Akhlak Siswa - Siti Maria Ulpa; Lubna; Mukhlis (Mataram University, 2026)
In the era of the independent curriculum, Islamic Religious Education (PAI) learning is no longer merely theoretical in the classroom; it must actually transform behavior and shape students' morals. This study aims to determine how transforming the evaluation of Islamic Religious Education (PAI) learning can shape students' morals. This study used a descriptive qualitative approach, with Islamic Religious Education (PAI) teachers at SMP Negeri 2 Sembalun, East Lombok as subjects. Data were collected through interviews, observations, and documentation of student projects, specifically activities involving processing waste into economically valuable crafts. The results showed that project-based Islamic Religious Education (PAI) learning not only improved students' skills and creativity but also instilled moral values such as responsibility, cooperation, environmental stewardship, honesty, discipline, independence, and decision-making skills. Project-based evaluation provides a more comprehensive picture of student character development than conventional evaluation. The waste recycling project activity is an effective means of instilling Pancasila values while providing students with real-life experiences that directly connect learning, creativity, and moral strengthening.